Income inequality & redistributional spending: An empirical investigation of competing theories - Philipp Mohl; Oliver Pamp (Luxembourg Income Study (LIS), 2008)
The link between income inequality and governmental redistribution is still subject to intense research and debate. Starting with the median-voter-hypothesis, a plethora of theoretical models have been developed during the last three decades to identify and explain possible causal relationships. The empirical evidence so far, however, has been mixed. The aim of this paper is to review the existing literature on inequality and redistribution, to explicate the theoretical causal mechanisms identified so far, and to provide a comprehensive and rigorous empirical test that overcomes some of the shortcomings of previous empirical studies. Using panel data on 23 OECD countries over the time period of 1971-2005, we not only look at different spending categories but also at the share gains of different income deciles and the median-to-mean ratio. We find robust evidence that income inequality affects redistribution. However, the precise degree of this relationship differs for different parts of the income distribution.
Keywords: C23; D33; D72; H11; H53; 330; redistribution; income inequality; median voter models; panel data; Einkommensverteilung; Einkommensumverteilung; Medianwähler-Modell; Panelforschung; Theorie; OECD-Staaten